POTENSI STRETCHING BERBASIS TEKNOLOGI DAN DIGITAL UNTUK MENINGKATKAN FLEKSIBILITAS: KAJIAN LITERATUR MUTAKHIR - Andriano Pandapotan Manik; Aulia Aditama; Nadia Mentari; Randi Sihombing; Nurhayati Simatupang (STKIP Subang, 2026)
Flexibility is an essential component of physical fitness for athletes, office workers, elderly individuals, and those with mobility limitations. With the rapid advancement of digital technology, various innovations including mobile applications, wearable devices, Virtual Reality (VR), Augmented Reality (AR), artificial intelligence (AI), gamification, video-guided stretching, and tele-stretching platforms have emerged as alternatives or complements to conventional stretching exercises. This literature review aims to critically analyze the potential, effectiveness, advantages, and limitations of digital technologies in improving muscle flexibility and Range of Motion (ROM) across diverse populations. A systematic literature review methodology was applied to scientific articles published between 2018 and 2026, sourced from PubMed, Scopus, Google Scholar, and DOAJ using structured keywords. Results indicate that digital stretching technologies effectively improve ROM by 12–22% compared to baseline, with higher exercise adherence than conventional methods in certain population groups. Nevertheless, limitations such as device costs, technology learning curves, and limited validation in elderly populations remain primary challenges. Future research is recommended to develop large-scale randomized clinical trials to consolidate existing scientific evidence.